(untitled) (Studia Prawnicze / The Legal Studies, 2023)
1. The theory of power division is utopian because the whole power of the state is in hands of the ruling class, which does not share it with anybody else and, what is more, it can not be shared with anybody otherwise, the ruling class would loose the status of the ruling one. However, rejecting the theory of power division, as inconsistent with the reality (state power unity), Marxism perceives the rational character of this theory in the fact that it fosters the useful and effective labour division in the state machanism. 2. The lawyers’ independence guarantee may be different. In many western countries lawyres are appointed for their life-time. In the majority of the socialist countries lawyers are elected for a definite period of time. Another system is adopted here. Both systems of the lawyers’ corps recruitment- have their advantages and disadvantages. 3. Independence of lawyers and their subordination to the regulation exclusively, means that a lawyer can not doubt the correctness and just of the regulation in force. In the Greek report, however, it is stated that a lawyer should not apply the regulation which is inconsistent with the constitution. It seems that this position can not be accepted. A lawyer is not entitled to control a legislator (excluding the so-called constitutional courts which are directly entitled to investigate the consistency of regulations with the constitution). 4. A litiyable problem of law of the power organ of the higher rank to abrogate or to change the sentence in a definite case should be solved in the following way. The legal activity should be permitted only by the legal organs: it can not be passed on, even exceptionally, to any other state organ, including the parliament. The supreme body of the state organ is entitled to control solely a legal act of a general nature, for example: the guide-lines of the judicature. But it should not in any definite case substitute the court. 5. One of the important judicature’s guarantees is a full description of all kinds of court existing in the country, i.e. the court system, and specifying them in the constitution. If such a specification is included in the constitution (it is like that in the Soviet Union, Czechoslovakia, East Germany, Romania) no other courts can be brought to life, and the issue of a separate bill on the matter will not be sufficient. It could only be done by means of changing the constitution. The court hierarchy specified in the constitution brings the stability of the judicature system and positively influences the regime of law observation and creates a. supplementary guarantee of the rights of an individual. 6. In the final part of the article the social courts are analysed and the mutual relation of the principle of collegiality and one-man activity in the work of courts is examined. The participation of non-professional judges in judicature is also considered.